Mortality of NAFLD According to the Body Composition and Presence of Metabolic Abnormalities. Issue 8 (19th May 2020) - Golabi, Pegah; Paik, James M.; Arshad, Tamoore; Younossi, Youssef; Mishra, Alita; Younossi, Zobair M.
Abstract : Although nonalcoholic fatty liver disease (NAFLD) is associated with obesity, it can also occur in lean and metabolically normal individuals. Our aim was to determine the effect of different combinations of abdominal adiposity and overall adiposity on the mortality of NAFLD. The Third National Health and Nutrition Examination Survey with mortality data from the National Death Index were used. NAFLD was defined as steatosis without other liver diseases. Body composition was categorized according to waist circumference (WC) and body mass index (BMI). Obesity pattern was defined according to BMI (lean, overweight, and obese) and WC (normal and obese) using accepted definitions. The "metabolically abnormal" group had visceral obesity, insulin resistance, type 2 diabetes, hypertension, or hyperlipidemia. Of the 9, 341 study individuals (47.9% male; 76.8% white), NAFLD was present in 3, 140 (33.6%), of whom 0.6% had lean BMI and normal WC, and 1.7% had lean BMI and obese WC. The prevalence of metabolically normal NAFLD was 3.26% (95% confidence interval [CI]: 2.62%‐3.90%), with most of these subjects having lean BMI (79.2%). During an average follow‐up of 22.4 years, 24.1% of the subjects died from all causes. Among these deceased individuals, 41.7% had NAFLD at baseline. Causes of death were cardiovascular disease (24.8%), cancer‐related (24.3%), type 2 diabetes–related (4.4%), and liver‐related (1.7%). Individuals with NAFLD who were lean by BMI but obese by WC had higher risk of all‐cause mortality. Individuals with NAFLD with normal BMI but obese WC had a higher risk of cardiovascular mortality (hazard ratio 2.63 [95% CI: 1.15‐6.01]) as compared with overweight (by BMI) NAFLD with normal WC. Conclusion: The risk of mortality in NAFLD can be affected by the presence of visceral obesity, especially in the lean BMI group. These data have important management implications for patients with NAFLD. Abstract :